Direct theory : experimental film/video as major genre - Small, Edward S., 1939- (Southern Illinois University Press, 1994)
"Acting as a classic apologist for an overlooked and misunderstood category of work, Edward S. Small has produced a historical/theoretical survey of that international body of film and (more recently) video loosely labeled "avant garde."" "In six chapters, Small surveys the entire development of experimental film, covering seven decades from its beginnings in the European avant garde movement, tracing this development through American underground production and international structuralist works, and ending with the experimental videos of the 1990s. Interwoven throughout is a discussion of concomitant classic and contemporary written film theory."--Jacket